Unveiling Tumor Microenvironment Interactions Using Zebrafish Models - Loveless, Reid; Shay, Chloe; Teng, Yong (Frontiers in Molecular Biosciences, 2021)
The tumor microenvironment (TME) is a rich and active arena that is strategically evolved overtime by tumors to promote their survival and dissemination. Over the years, attention has been focused to characterize and identify the tumor-supporting roles and subsequent targeting potentials of TME components. Nevertheless, recapitulating the human TME has proved inherently challenging, leaving much to be explored. In this regard, in vivo model systems like zebrafish, with its optical clarity, ease of genetic manipulation, and high engraftment, have proven to be indispensable for TME modeling and investigation. In this review, we discuss the recent ways by which zebrafish models have lent their utility to provide new insights into the various cellular and molecular mechanisms driving TME dynamics and tumor-support. Specifically, we report on cytokine signaling, innate immune cell interactions, metastatic plasticity, and other processes within the metastatic cascade. In addition, we reflect on the arrival of adult zebrafish models and the potential of patient-derived xenografts.